Adults Hemoglobin Level in Atiafa Primary Health Care Center in Najran Area (5-7)/1433 H - ALFARAN, FAHAD; ALDOSARI, SULTAN (International Journal of Innovative Research in Medical Science, 2017)
The aim of this study was to estimate hemoglobin Level among adults in Atiafa Primary Health Care Center in Najran Area, Saudi Arabia (5-7)/1433 H. A total of 90 adults were recruited of which, 48 were females and 42 were males. Male subjects were reclassified to cigarette smokers (n =18) and non-smokers (n = 24). Female subjects were reclassified to pregnant women (n =22) and non-pregnant women (n = 26). Anemia was assessed by hemoglobin level. The results showed that, hemoglobin level was significantly higher in males compared to females. Mean concentration of hemoglobin (15.064g/dL) for males was normal. Hemoglobin level was significantly higher in smokers compared to non-smokers, but both were normal, which suggested that anemia is not found among adults males sample. Mean hemoglobin level (12.10g/dL) of non-pregnant women was lower than cutoff value for determining anemia (low hemoglobin level). Based on hemoglobin value, 50.2% of female participants were anemic. Mean hemoglobin level of pregnant women was (10.98g/dL). A total of 24 adults non-smokers were reclassified to obese adults (n =10) and non-obese adults (n = 14). No significant different hemoglobin Level in obese adults as compared with non-obese adults. Results of this study illustrated that anemia is highly prevalent among adults pregnant and non-pregnant women in Atiafa Primary Health Care Center in Najran Area, Saudi Arabia and suggests actions to eradicate anemia. These actions include increasing nutritional awareness and education for the purpose of changing inappropriate consumption patterns as well as fortification of certain foods in combination with nutritional program for pregnant women.